Analisis Kualitas Jaringan Internet 4G Menggunakan Metode Quality of Service - Ibrahim Armadian Pujakesuma; Iwan Iskandar; Novriyanto; Pizaini (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
This study aims to evaluate the quality of the 4G internet network in Tuah Madani District using the Quality of Service (QoS) method which involves throughput, packet loss, delay, and jitter parameters. Due to the high population level, the Tuah Madani sub-district has a densely populated area with a significant population. This causes the need for high internet services as well. The high population density can affect the quality of the network, where the density of the population and the large number of buildings can cause network performance to be less than optimal. The purpose of this study is to provide comprehensive information about the quality of the 4G internet network in Tuah Madani District and provide recommendations to the public to choose the best provider. Analysis of the quality of the 4G network was carried out in three urban villages with the largest population, namely West Sidomulyo Village, Tuah Karya Village, and Sialang Munggu Village. The results of the study in West Sidomulyo Village showed that Smartfren was the best provider with an index value of 4 and received the "Very Good" category. The results of the study in the Tuah Karya Village showed that Telkomsel was the best provider with an index value of 4 and received the "Very Good" category. The results of the study in the Sialang Munggu Village showed that Smartfren was the best provider in the Sialang Munggu Village with an index value of 4 and received the "Very Good" category